2012
DOI: 10.1039/c2ay05934g
|View full text |Cite
|
Sign up to set email alerts
|

Platinum screen printed electrodes for the electroanalytical sensing of hydrazine and hydrogen peroxide

Abstract: We report the fabrication of platinum screen printed electrodes which are electrochemically characterised and evaluated as to their potential analytical application towards the sensing of hydrazine and hydrogen peroxide. In the case of hydrazine a linear range of 50 to 500 mM is possible with a limit of detection (3s) of 0.15 mM achievable using cyclic voltammetry which can be reduced to 0.12 mM using chronoamperometry. The novelty of these platinum screen printed electrodes is highlighted in that the platinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 71 publications
(63 reference statements)
1
27
0
Order By: Relevance
“…The linear detection range is estimated to be from 5 to 900 μM (r=0.999), and the detection limit is estimated to be 0.08 μΜ at a signal-to-noise ratio of 3. Note that our present sensing system gives lower detection limit than that of platinum screen-printed electrodes (0.12 μM) [42], AuNPs on thiolated single-stranded DNA-modified Au electrode (0.56 μM) [43], and hybrid nickel hexacyanoferratefunctionalized multiwalled carbon nanotube/GCE [44].…”
Section: Determination Of Glucose At God/aunps/rgo/gcementioning
confidence: 99%
“…The linear detection range is estimated to be from 5 to 900 μM (r=0.999), and the detection limit is estimated to be 0.08 μΜ at a signal-to-noise ratio of 3. Note that our present sensing system gives lower detection limit than that of platinum screen-printed electrodes (0.12 μM) [42], AuNPs on thiolated single-stranded DNA-modified Au electrode (0.56 μM) [43], and hybrid nickel hexacyanoferratefunctionalized multiwalled carbon nanotube/GCE [44].…”
Section: Determination Of Glucose At God/aunps/rgo/gcementioning
confidence: 99%
“…17,18 However, it is often a key impurity in pharmaceutical products, and its high toxicity has led to the development of (electrochemical) hydrazine sensors. [19][20][21] Voltammetric and amperometric hydrazine analysis is usually performed in air and the role of oxygen in hydrazine detection is rarely taken into account. 22 This is an important consideration, because hydrazine can (catalytically) reduce oxygen on various surfaces, a process that is exploited for corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Carbon-based SPEs usually perform well in aqueous solvents and show similar electrode kinetics to those observed on conventional disk-electrodes. [4,5,6] Gold [7,8] and platinum [9,10] SPEs have also been used, but much more rarely. Moving away from experiments in aqueous-based solvents, we recently found that the background currents of DropSens carbon SPEs are very large compared to Pt and Au SPEs when room temperature ionic liquid (RTIL) solvents are employed.…”
Section: Introductionmentioning
confidence: 99%